Dekonstruksi Tubuh Perempuan dalam Iklan Kondom Fiesta pada Peringatan Hari AIDS Sedunia 2025 - Hadi Utomo, Samuel Rihi; Sentani, Elizabeth Jessica; Rahmawaty (Universitas 17 Agustus 1945 Surabaya, 2026)
This study analyzes the deconstruction of the female body in the 2025 World AIDS Day advertisement produced by Fiesta Condoms in Indonesia. Situated within a socio-cultural context where patriarchal norms continue to shape women’s vulnerability to HIV, particularly among housewives, this research examines how visual media negotiates gender, sexuality, and responsibility in sexual health campaigns. Employing a qualitative interpretive approach, the study integrates deconstruction as a critical framework (Saukko, 2003) with multimodal social semiotics (Kress and van Leeuwen) to analyze how meaning is constructed across visual, textual, and auditory modes. Through the analysis of representational, interactive, and compositional meanings, the study identifies a shift from the traditional objectification of women toward their construction as sexually assertive and agentic subjects who actively negotiate condom use. This shift appears to challenge dominant gender binaries such as passive/active and object/subject. However, a deconstructive reading reveals that such empowerment remains ambivalent, as female agency is simultaneously embedded within dominant beauty norms, heteronormative relationships, and market-oriented logics that regulate its expression. In particular, the study highlights the emergence of commodity feminism, in which empowerment is articulated through consumption. The representation of a young, modern, and financially independent female figure functions to reposition women as potential consumers of condoms, thereby expanding the market while subtly shifting responsibility for sexual health onto women. This study contributes to media and gender scholarship by demonstrating how advertising both disrupts and reproduces gendered power relations. Keywords: deconstruction; female body; gender binary; multimodality; advertising